Rhamnan Sulfate from the Seaweed Monostroma nitidum May Improve Cognitive Impairment Caused by Hyperglycemia - Takaichi Miwa; Masaya Sato; Ning Ma; Keiichi Hiramoto; Masahiro Terasawa; Koji Suzuki (Marine Drugs)
Rhamnan sulfate (RS), extracted from the seaweed Monostroma nitidum, suppresses vascular endothelial inflammation and arteriosclerosis, decreases blood glucose levels, and improves blood lipid metabolism and the intestinal environment. We examined whether RS improves hyperglycemia-induced cognitive decline in a hyperglycemic mouse model pretreated with nicotinamide and streptozotocin and then orally administered a high-fat diet and maltodextrin (MD) for 4 months. RS was administered in an MD solution at doses of 75, 225, and 750 mg/kg of mouse body weight. Administration of RS to hyperglycemic mice significantly reduced blood glucose levels and tended to improve memory function in behavioral pharmacological tests using spontaneous locomotor activity, rotarod test, and eight-way-maze test, although the results were not significant. Brain histopathological analysis showed that RS significantly reduced atrophy of neuronal layers in each region of the hippocampus compared with untreated hyperglycemic controls. RS also significantly suppressed TNF-α expression and microglial activation in the brain. These results suggest that RS intake suppresses inflammation in the brain and alleviates the cognitive impairment associated with hyperglycemic diabetes.